РLАNNING АND DЕSIGNING ЕNGАGING LЕSSONS (International journal of artificial intelligence, 2025)
This article investigates the planning and designing of engaging lessons within the context of modern language teaching methodologies. As language education evolves, there is a growing need for innovative and learner-centered approaches that promote motivation, engagement, autonomy, and critical thinking. The study explores the principles and practices of effective lesson design by focusing on methods such as Task-Based Language Teaching, Project-Based Learning, and Content and Language Integrated Learning. It analyzes how these approaches necessitate a reconceptualization of traditional planning strategies to foster authentic communication and active learning. Key factors influencing lesson planning—such as teacher expertise, curriculum constraints, and technological integration—are examined. The dissertation aims to provide practical guidance to educators and curriculum developers by bridging theoretical frameworks like Understanding by Design and differentiated instruction with classroom application. The findings highlight both the potential and the challenges of implementing engaging lesson plans and offer insights for enhancing educational practice in contemporary language classrooms.